An in vitro analysis of an innovative standardized phospholipid carrier-based Melissa officinalis L. extract as a potential neuromodulator for emotional distress and related conditions - Kara, Mehtap; Sahin, Sumeyye; Rabbani, Fazle; Oztas, Ezgi; Hasbal-Celikok, Gozde; Kanımdan, Ebru; Kocyigit, Abdurrahim; Kanwal, Ayesha; Wade, Ursula; Yakunina, Anastasia; Di Pierro, Francesco; Khan, Amjad (Frontiers in Molecular Biosciences, 2024)
Melissa officinalis L. (MO) commonly known as Lemon balm, a member of the mint family, is considered a calming herb. In various traditional medicine, it has been utilised to reduce stress, anxiety, and promote sleep. A growing body of clinical evidence suggests that MO leaf extract supplementation possesses considerable neuropharmacological properties. However, its possible mechanism largely remains unknown.In the present in vitro studies, we comparatively investigated the central nervous system (CNS) calming and antioxidative stress properties of a standardized innovative phospholipid carrier-based (Phytosome™) MO extract (Relissa™) vs an unformulated dry MO extract.Extracts neuropharmacological effects were studied in the anti-depressant enzymes γ-aminobutyrate transaminase (GABA-T) & monoamine oxidase A (MAO-A) assays, and SH-SY5Y cells brain-derived neurotrophic factor (BDNF) expression assay. Extracts neuroprotective effect against oxidative stress was assessed in SH-SY5Y cells-based (H2O2-exposed) Total Anti-oxidant Status (TAS) and Totalreactive oxygen species (ROS) assays. Extracts cytotoxic effects were evaluated using MTT and LDH assays. Anti-oxidant effects were also evaluated in cells free chemical tests including TEAC-ABTS, DPPH, Ferric reducing antioxidant power (FRAP), Oxygen Radical Antioxidant Capacity (ORAC), and Hydroxyl Radical Antioxidant Capacity (HORAC) assays.Relissa™ exhibited high GABA-T inhibitory activity, IC50 (mg/mL) = 0.064 vs unformulated dry MO extract, IC50 (mg/mL) = 0.27. The same was true for MAO-A. Relissa™ demonstrated improved neuroprotective antioxidant effect on SH-SY5Y cells against H2O2-induced oxidative stress. In comparison to unformulated dry MO extract, Relissa™ showed high potency increasing SH-SY5Y cells BDNF expression levels upon exposure to H2O2. Moreover, cell free chemical tests including, TEAC-ABTS, DPPH radical scavenging, FRAP, ORAC, and HORAC assays validated the improved antioxidant effect of Relissa™ vs unformulated dry MO extract.The results of the present study supports the neuromodulating and neuroprotective properties of Relissa™, and its supplementation may possibly help in the amelioration of emotional distress and related conditions.